Telescope performance and image simulations of the balloon-borne coded-mask protoMIRAX experiment. Issue 5 (April 2016) - Penacchioni, A.V.; Braga, J.; Castro Avila, M.A.; Amico, F. D
Abstract: In this work we present the results of imaging simulations performed with the help of the GEANT4 package for the protoMIRAX hard X-ray balloon experiment. The instrumental background was simulated taking into account the various radiation components and their angular dependence, as well as a detailed mass model of the experiment. We modelled the meridian transits of the Crab Nebula and the Galactic Centre (GC) region during balloon flights in Brazil (∽ -23° of latitude and ∽ 40 km of altitude) and introduced the correspondent spectra as inputs to the imaging simulations. We present images of the Crab and of three sources in the GC region: IE 1740.7-2942, GRS 1758-258 and GX 1+4. The results show that the protoMIRAX experiment is capable of making spectral and timing observations of bright hard X-ray sources as well as important imaging demonstrations that will contribute to the design of the MIRAX satellite mission.